Rosacea: a clinical review - Carsten Sauer Mikkelsen; Helene Ringe Holmgren; Petra Kjellman; Michael Heidenheim; Ari Karppinnen; Peter Bjerring; Theis Huldt-Nystrøm (PAGEPress Publications, 2016)
Rosacea is a field within dermatology with new insight within immunological research and new treatment-algorithm. Patient education on rosacea and appropriate treatments is an important aspect in helping patients succeed with therapy. Treatment should be tailored to each individual patient, taking into account: symptoms, trigger factors, patients' wishes, most bothersome symptoms, psychological aspect, individual needs. A combination of clinical therapies to treat different symptoms concomitantly may offer the best possible outcomes for the patient. In this review article we describe these aspects.